2013
DOI: 10.1177/0093854813482309
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Canadian Youth-Perpetrated Homicides

Abstract: Youth-perpetrated homicide has considerable impact on our society and justice system. unfortunately, youth-perpetrated homicide is an understudied crime and even less research has been conducted specific to a Canadian population. two decades ago, Meloff and Silverman published the most thorough examination of youth-perpetrated homicide in Canada. Since that time, it has been proposed that the motivations and characteristics of youth violence have changed in a number of important ways. the present study expands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(119 reference statements)
1
9
0
Order By: Relevance
“…Prior research has found that many homicides occurred in the context of intimate relationships (Wilson and Daly 1985). Likewise, researchers have found that the likelihood of a homicide occurring with multiple offenders increased when the social distance between the victim and offender increased (Meloff and Silverman 1992;Woodworth et al 2013). We found this to be true, with the exception of female offenders when they offend with others.…”
Section: Discussionsupporting
confidence: 60%
“…Prior research has found that many homicides occurred in the context of intimate relationships (Wilson and Daly 1985). Likewise, researchers have found that the likelihood of a homicide occurring with multiple offenders increased when the social distance between the victim and offender increased (Meloff and Silverman 1992;Woodworth et al 2013). We found this to be true, with the exception of female offenders when they offend with others.…”
Section: Discussionsupporting
confidence: 60%
“…Drugs and/or alcohol were not used prior to or during the offense by over half of the female youth cohort in the current study, which is consistent with Carpenter's () primarily male, generally violent male youth sample. In contrast, the rate of youths not using drugs and/or alcohol prior to or during the offense drops drastically to 32.0% among youth homicide offenders (Woodworth et al ., ). While the use of alcohol or substances appears not to be as primary a contributor for these female youths' engagement in generally violent offenses (compared with homicides), it still appears to explain, at least partially, their behavior in a substantial number of cases.…”
Section: Discussionmentioning
confidence: 97%
“…The use of instrumental violence among youths who possess higher levels of psychopathic traits has also been demonstrated among youths responsible for severe criminal acts. For instance, among an almost exclusively male homicide offender sample, Agar () found that increases in PCL:YV scores were associated with increases in the likelihood of instrumentality (see also Woodworth et al ., ). The interpersonal and affective characteristics of psychopathy arguably distinguish psychopathy from comparatively less severe antisocial disorders (Rogstad & Rogers, ), and the results indicated that factor 1 was significantly correlated with instrumentality.…”
mentioning
confidence: 97%
See 2 more Smart Citations